ISLAMIC LEGAL FRAMEWORK FOR ENHANCING TAKAFUL IJTIMĀ‘Ī THROUGH WAQF-MUSHĀRAKAH MODELS IN INDONESIA AND MALAYSIA - Asyiqin, Istianah Zainal; binti Abul Hisyam, Ayesha (Jurnal Al-Dustur, 2026)
Sharia insurance (at-Takāful) is founded on the principle of mutual assistance (at-Takāful al-Ijtimā ‘ī), yet existing models often fail to ensure equitable outcomes. Most contemporary Sharia insurance practices rely on hybrid contracts (multi-ʿaqd), combining ʿAqd Tabarru‘ (charitable contribution) and ʿAqd Muḍārabah (profit-sharing). However, these approaches have limitations in achieving social justice. This study examines the integration of Waqf and Mushārakah models as alternative solutions to enhance fairness in Islamic insurance. While Indonesia’s Takāful system predominantly uses traditional hybrid contracts, Malaysia employs a more advanced Takāful framework, incorporating Waqf and Mushārakah to strengthen social justice and economic sustainability. Using a normative legal research approach, this study employs a doctrinal approach and compares Indonesian and Malaysian Takāful structures, analyzing the legal and economic implications of adopting Waqf and Mushārakah in Sharia insurance. The findings suggest that the Waqf model aligns with Islamic economic objectives such as poverty alleviation (raf‘ al-faqr) and wealth distribution (taqwīm al-tharwah), while Mushārakah fosters cooperative principles and equitable profit-sharing (al-ta‘āwun wa al-‘adālah al-māliyah). The study concludes that integrating Waqf and Mushārakah into Indonesia’s Sharia insurance system can enhance Takāful Ijtimā‘ī principles and promote greater financial justice in accordance with the Maqāṣid al-Sharī‘ah.